PENGGUNAAN PLC DALAM PENGONTROLAN TEMPERATUR, SIMULASI PADA PROTOTYPE RUANGAN - Erinofiardi, Erinofiardi; Supardi, Nurul Iman; Redi, Redi (Jurnal MEKANIKAL, 2012)
Programmable Logic Control is a automatic control device which has memory for storing input program to control devices or processes by using input module and outpu in digital or analogue. This research conduct using of PLC to control temperature in prototype room, by using Zelio logicÂ smart relay, and module sensor LM35. Prototype room is made from glass, with dimension 60mm x 20mm x 20mm and has roof like a house, and 4 fans are put on the long side of the room. From this experiment, based on temperature which set on FBD program, room temparature can be controlled in 320C succesfully.